Factor inhibiting HIF-1 (FIH-1) modulates protein interactions of apoptosis-stimulating p53 binding protein 2 (ASPP2) - Janke, Kirsten; Brockmeier, Ulf; Kuhlmann, Katja; Eisenacher, Martin; Nolde, Jan; Meyer, Helmut E.; Mairbäurl, Heimo; Metzen, Eric (Journal of cell science, 2013)
Skip to Next Section - The asparaginyl hydroxylase factor inhibiting HIF-1 (FIH-1) is an important suppressor of hypoxia-inducible factor (HIF) activity. In addition to HIF-α, FIH-1 was previously shown to hydroxylate other substrates within a highly conserved protein interaction domain, termed the ankyrin repeat domain (ARD). However, to date, the biological role of FIH-1-dependent ARD hydroxylation could not be clarified for any ARD-containing substrate. The apoptosis-stimulating p53-binding protein (ASPP) family members were initially identified as highly conserved regulators of the tumour suppressor p53. In addition, ASPP2 was shown to be important for the regulation of cell polarity through interaction with partitioning defective 3 homolog (Par-3). Using mass spectrometry we identified ASPP2 as a new substrate of FIH-1 but inhibitory ASPP (iASPP) was not hydroxylated. We demonstrated that ASPP2 asparagine 986 (N986) is a single hydroxylation site located within the ARD. ASPP2 protein levels and stability were not affected by depletion or inhibition of FIH-1. However, FIH-1 depletion did lead to impaired binding of Par-3 to ASPP2 while the interaction between ASPP2 and p53, apoptosis and proliferation of the cancer cells were not affected. Depletion of FIH-1 and incubation with the hydroxylase inhibitor dimethyloxalylglycine (DMOG) resulted in relocation of ASPP2 from cell-cell contacts to the cytosol. Our data thus demonstrate that protein interactions of ARD-containing substrates can be modified by FIH-1-dependent hydroxylation. The large cellular pool of ARD-containing proteins suggests that FIH-1 can affect a broad range of cellular functions and signalling pathways under certain conditions, for example, in response to severe hypoxia.
Gesehen am 25.03.2021